Utilization of Canva as Arabic Language Learning Media in the Industrial Revolution 4.0 Era - Fakhrurrozi, Fakhrurrozi; Kurniawan, Ilham; Syauqiah, Zulfa; Hilmi, Danial; Fadlilah, Nurul (UAS PRESS, 2026)
This study aims to describe the use of Canva as a medium for learning Arabic. This study uses a descriptive qualitative method. The instruments used by the researcher in data collection were interviews, observation, and documentation. The results of this study indicate that the use of Canva in Arabic language learning is able to meet the need for visualization of Arabic language learning materials in a concrete and structured manner, although there are still technical obstacles such as internet connection, device limitations, and premium features. This study also confirms that Canva has strong relevance in strengthening students' digital literacy in the era of the Industrial Revolution 4.0 because it not only facilitates access to technology but also encourages the development of creativity, collaboration, and visual communication skills as 21st-century competencies.